The effect of using an educational bag In acquiring and retaining geographical concepts For middle school students (Journal of the College of Basic Education, 2023)
The field of teaching the concepts of social subjects has witnessed an update in the methods, methods and tools of learning and the acquisition of concepts, especially after modern education has proven that traditional teaching methods are nothing but a dedication to knowledge and an increase in memorization and the lack of interaction of the student with what he has learned and the lack of employment of that knowledge in daily life, and this is what hindered the process Learn and retain concepts.That is why the trend began in recent decades towards concepts, teaching them, and paying attention to the methods that learners learn, and this is what encouraged many educators to develop effective educational models and strategies for the purpose of assisting teachers in their learning of the concepts they teach.Through the researcher's review of the studies and literature on learning concepts, he found agreement among most designers of educational models on strategies that represent educational and educational goals, which is to give importance to the autonomy of the learner, and to make him an active focus in the educational process through his effective contribution to the process of learning and teaching the concept.This prompted the researcher to present a new educational model, based on one of the self-learning strategies, which is the educational portfolio, in the hope that the results will contribute to moving the educational process forward.